Nishkama Karma and Practical Morality: A Critical Essay on Applied Ethics in Utkal Studies in Philosophy - KochappiIly, Paulachan (Journal of Dharma, 2000)
Rajendra Prasad Varnadharma, Nishkama Karma and Practical Morality. A Critical Essay on Applied Ethics in Utkal Studies in Philosophy, VI/, New Delhi: D.K. Printworld (P) Ltd., 1999, pp. Xii+291, ISBN 81-2460125-9, Rs.380.